Smartweaver: Aspect-Oriented Development using the Smartbooks Approach - Díaz Pace, Jorge Andrés (2002)
The aspect paradigm is now recognized as an important level of software development, however, the diversity of AOP approaches often requires from developers an important grasp of experience and programming skills in order to implement aspect-based functionality. AOP approaches are usually materialized in terms of specific languages or frameworks. In this work, we aim at providing smart guidance to developers to better take advantage of aspect facilities. We present an agent-based tool called Smartweaver, which allows developers to describe aspect designs using a special documentation method, and then provides assistance to translate these specifications into particular AOP implementation technologies.